Hypovitaminosis D and osteopenia/osteoporosis in a haemophilia population: a study in HCV/HIV or HCV infected patients. (9th July 2012) - Linari, S.; Montorzi, G.; Bartolozzi, D.; Borderi, M.; Melchiorre, D.; Benelli, M.; Morfini, M.
Summary Recent reports show a correlation between haemophilia and osteoporosis. HIV, HCV and their treatments are independently associated with an increased risk of osteoporosis. Vitamin D plays a pivotal role in bone mineralization. The aim of our study was to compare Vitamin D levels, bone metabolism markers and bone mineral density (BMD) in patients with haemophilia with or without co‐infections. Seventy‐eight adult patients with severe or moderate haemophilia A or B were subdivided into three groups of 26 patients each (HIV‐HCV co‐infected, HCV mono‐infected and uninfected). The BMD was measured by dual energy X‐ray absorptiometry (DXA) at both the femoral area (F) and lumbar spine (L). This was correlated to laboratory values and haemophilic arthropathy was assessed using validated clinical and radiological scores. The DXA showed a homogeneous F‐BMD reduction in all the three groups, whereas L‐BMD was significantly lower in co‐infected patients (P < 0.05). The clinical score was higher in co‐infected (P < 0.002) and mono‐infected (P < 0.006). The radiological score was higher in mono‐infected than in the other two groups (P < 0.001). Overall 25‐hydroxyvitamin D (25‐OH Vit D) was reduced (87%). Bone‐specific alkaline phosphatase (b‐ALP) and telopeptide were increased in co‐infected (P < 0.001 and P < 0.01) and mono‐infected (P < 0.001 and P < 0.02). The result of the homogeneous F‐BMD reduction in all groups could be explained by the pivotal role of arthropathy; the lower L‐BMD in co‐infected and the increase of b‐ALP and telopeptide in co‐infected and mono‐infected groups suggest faster bone metabolism in case of infections.